2021
DOI: 10.3390/su13073996
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Selected Intelligent Systems in Logistics on the Creation of a Sustainable Market Position of Manufacturing Companies in Poland in the Context of Industry 4.0

Abstract: Within the broadly understood concept of Industry 4.0, many intelligent systems featuring artificial intelligence are used. Their importance in recent years has been growing. That can be attributed to a number of notable advantages these systems provide, including the possibility of expanding the manufacturer’s offer, greater customization of products, which facilitates reaching niche markets, as well as better internal and/or external communication (between the company and the consumer). Six such systems are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 34 publications
1
4
0
1
Order By: Relevance
“…Feasible mid-and long-term intellectual property development plans and goals are formulated according to the enterprise’s development goals, operating conditions, competitive landscape, and market development trends (Vecchiato 2020 ). Previous reports have taken the strategy of intellectual property as an essential measurement indicator for evaluating an enterprise’s innovation capability (Stanisławski and Szymonik 2021 ; Jiang et al 2021 ). Information system: it tracks and predicts technological trends, industry trends, competitive areas, and market trends, providing a decision-making basis for formulating the enterprise’s research and development plan, thereby determining the enterprise’s product development goals.…”
Section: Analysis Of Intelligent Innovation Of Open Technologies Unde...mentioning
confidence: 99%
“…Feasible mid-and long-term intellectual property development plans and goals are formulated according to the enterprise’s development goals, operating conditions, competitive landscape, and market development trends (Vecchiato 2020 ). Previous reports have taken the strategy of intellectual property as an essential measurement indicator for evaluating an enterprise’s innovation capability (Stanisławski and Szymonik 2021 ; Jiang et al 2021 ). Information system: it tracks and predicts technological trends, industry trends, competitive areas, and market trends, providing a decision-making basis for formulating the enterprise’s research and development plan, thereby determining the enterprise’s product development goals.…”
Section: Analysis Of Intelligent Innovation Of Open Technologies Unde...mentioning
confidence: 99%
“…It is easier to obtain the necessary resources related to the implementation of new (even more innovative) solutions. In addition, such a location allows them to enter new markets, and thus access to customers requiring the highest quality logistics service, who emphasize efficiency, comprehensiveness, or speed of services (Stanisławski and Szymonik, 2021). This thesis is confirmed by the list presenting the market coverage of the surveyed companies.…”
Section: Characteristics Of the Research Samplesupporting
confidence: 52%
“…In general, it can be concluded that the environment (partners) does not create conditions that would enable the exchange of resources resulting in an increase in the propensity to implement IoT among Polish manufacturing companies. The reasons for this situation can probably be seen in the context of the competitive game, the measurable effect of which is to be the elimination of competition (Stanisławski and Szymonik, 2021). Therefore, when answering the first research question, it should be stated, firstly, that internal conditions are perceived as definitely greater barriers to the implementation of IoT than external ones.…”
Section: Barriersmentioning
confidence: 99%
See 1 more Smart Citation
“…A service charge is a fee that is incurred to obtain services, including digital banking services (Broby, 2021). According to Eldeeb, Halim & Kamel (2021) and Stanislawski & Syzmonik (2021), the nominal amount of business or money spent using digital banking services, including the comparison with the benefits obtained, determines using a sustainable service system (ElDeeb, Halim, & Kamel, 2021;Stanisławski & Szymonik, 2021). The hypothesis testing of several previous studies uncovered that service charges significantly affected customer satisfaction due to the desire for a return on effort (Chien & Chi, 2019;Lynn & Brewster, 2018;Nyarku et al, 2018).…”
Section: Hypotheses Developmentmentioning
confidence: 99%